The Use of Demonstration Methods in Learning Cultural Arts (Theater) in Class X E 1 SMA Negeri 7 Padang - Vanesa, Abelita Khre; Susmiarti (Universitas Negeri Padang, 2023)
The purpose of this study was to describe the demonstration method in learning arts and culture (theatre) in class X E 1 SMA Negeri 7 Padang. This type of research is qualitative research with descriptive methods. The research tools are the researchers themselves, and tools such as stationery and cameras are very helpful. Primary data and secondary data are used in this research material. Data collection techniques were carried out through literature studies, observations, interviews and documentation. The steps to analyze the data are classifying data, clarifying data, analyzing data, describing data, and concluding data. The results of the research and discussion concluded that the learning methods were appropriate and the results of the students' scores had increased sufficiently. The implementation of cultural arts learning (theatre) with the demonstration method in class X E 1 SMA Negeri 7 Padang has a great influence on student learning and therefore helps to increase the willingness to learn, participation and results of learning arts and culture (theater) in class X E 1. Although there are still students who do not present the results of the monologue in accordance with a predetermined technique.